A Routine PET/CT Protocol with Streamlined Calculations for Assessing Cardiac Amyloidosis Using 18F-Florbetapir - Osborne, Dustin R.; Acuff, Shelley N.; Stuckey, Alan; Wall, Jonathan S. (Frontiers in Cardiovascular Medicine, 2015)
Introduction: Cardiac amyloidosis is a rare condition characterized by the deposition of well-structured protein fibrils, proteoglycans, and serum proteins as amyloid. Recent work has shown that it may be possible to use 18F-Florbetapir to image cardiac amyloidosis. Current methods for assessment include invasive biopsy techniques. This work enhances foundational work by Dorbala et al. by developing a routine imaging and analysis protocol using 18F-Florbetapir for cardiac amyloid assessment. Methods: Ten patients, 3 healthy controls and 7 amyloid positive patients, were imaged using 18F-Florbetapir to assess cardiac amyloid burden. Four of the patients also were imaged using 82Rb-Chloride to evaluate possible 18F-Florbetapir retention because of reduced myocardial blood flow. Quantitative methods using modeling, SUVs and SUV ratios were used to define a new streamlined clinical imaging protocol that could be used routinely and provide patient stratification. Results: Quantitative analysis of 18F-Florbetapir cardiac amyloid data were compiled from a 20 minute listmode protocol with data histogrammed into two static images at 0-5 minutes and, 10-15 min or 15-20 min. Data analysis indicated the use of SUVs or ratios of SUVs calculated from regions draw in the septal wall were adequate in identification of all healthy controls from amyloid positive patients in this small cohort. Additionally, we found that it may be possible to use this method to differentiate patients suffering from AL vs. TTR amyloid. Conclusions: This work builds on the seminal work by Dorbala et Al. by describing a short 18F-Florbetapir imaging protocol that is suitable for routine clinical use and uses a simple method for quantitative analysis of cardiac amyloid disease.